Fuzzy Delphi Method For Developing Arabic Speaking Learning Module for Nursing Students/ Metode Fuzzy Delphi Untuk Pengembangan Modul Pembelajaran Berbicara Bahasa Arab bagi Mahasiswa Keperawatan - Khairul Huda Jaya; Zawawi Ismail (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The ability of health workers to communicate in foreign languages is a current professional demand in carrying out their duties. The concept of communicative language teaching is considered effective in realizing the ability of nurses as health workers to communicate in Arabic for specific purposes. The use of speaking learning modules in Arabic for nursing students is one of the learning strategies that can support a communicative language teaching system to the needs of their profession as nurses. This study aimed to obtain expert agreement on various elements in designing and developing Arabic-speaking learning modules for nursing students. This study used the Fuzzy Delphi method to get consensus from the experts. The application of the method involved 14 experts in Arabic education from six different universities. The results of this study found that experts have reached a consensus on 26 tested items with an average value below the Threshold (d) of 0.2. The consensus percentage also showed scores above 75% on the 26 items. Meanwhile, only one item was rejected because it obtained a Threshold (d) value above 0.2 and a percentage value below 75%. Arabic language teachers and nursing students can use the results of this study as module users. They can also be a reference for researchers and developers of the next module.